A relação entre o engajamento esportivo e os desempenhos psicológicos dos jogadores de futebol no período pandêmico: exemplo da liga regional de amadores - Arisoy, A.; Pepe, O. (Lex Humana, 2021)
The aim of this study is to examine the relationship between sport engagement and psychological performances of football players during the pandemic period. 179 players, who were selected randomly from 758 active players participating in trainings in 30 football teams joining leagues in the 4th region of Turkish Football Federation regional amateur league, participated in the study voluntarily. In the study, as a data collection tool, personal information form, sport engagement and psychological performance scales were used. In order to collect data, the Google Forms platform was preferred in order to maintain social distance during the pandemic priod. During the data collection period, information and questionnaires about the study were forwarded to the participants through social networks. SPSS 22 statistical package program was used to analyze the data. The arithmetic mean and standard deviation of the scores of football players from the scales are presented as X ± Sd. In order to reveal the relationship between the scores obtained from the scales, Pearson product moment correlation analysis (r) was applied. As a result, it was determined that the sport engagement and psychological performance levels of the regional amateur league players participating in the study during the pandemic priod were above average. When the sub-dimensions of psychological performance were examined, it was found that they were at the level of special attention. While there was no relationship between sport engagement and psychological performance total score and self-confidence sub-headings, negative correlations were found between negative energy and attention control, and a low level positive correlation was found between the sub-headings of visualization and imagery control, motivation level, positive energy and attitude control. It is thought that this is due to the fact that the pandemic priod does not seem to end soon and the league competitions to be played in this priod are postponed indefinitely.